Diffusion through porous media: ultrafiltration, membrane permeation and molecular sieving - Ruthven, Douglas M. (Diffusion Fundamentals, 2009)
This paper considers permeation through microporous or nanoporous inorganic membranes under the influence of an applied pressure gradient. In general membrane permeation may be considered as a diffusive process, driven by the gradient of chemical potential (which depends on both composition and pressure). The relative importance of these two factors varies greatly for different types of system. The general features of such processes are reviewed and the diffusional behavior of selected systems is examined (membrane permeation, osmosis, diffusion, zeolite membrane, DDR-3, SAPO-34).